THE EFFECT OF INNOVATIVENESS ON THE RELATIONSHIP BETWEEN DIVERSIFICATION AND SLACK - Fuad Fuad (EKUITAS (Jurnal Ekonomi dan Keuangan), 2012)
The main purpose of this paper is to investigate the management’s willingness to act in the best interest of the top corporate. Particularly, this study examines the role of incentive schemes to reduce the presence of budgetary slack in the business units budget. Pilot study was conducted to 34 respondents that represented the sample of this study to ensure the feasibility and clarity of questionnaires and collected comments from them. Using Moderated Structural Equation Modeling, this study found that diversified firms can not control the presence of budgetary slack. Moreover, this study found that the significance relationship between diversification and budgetary slack was moderated by the firms’ value orientation towards innovation. The results also revealed that, out of three incentive schemes, only corporate-based incentive was able to reduce the presence of budgetary slack. This paper suggest interested researcher to use other measures of incentives such as group-based versus tournament-based incentive. This study can be concluded that agency perspectives may no longer be suitable to explain the presence of budgetary slack in their business units as the nonsignificant effect found on the relationship between incentive schemes on budgetary slack.